2020
DOI: 10.1136/gutjnl-2020-323277
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an outreach, grouping healthcare system to achieve microelimination of HCV for uremic patients in haemodialysis centres (ERASE-C)

Abstract: ObjectiveHCV prevails in uremic haemodialysis patients. The current study aimed to achieve HCV microelimination in haemodialysis centres through a comprehensive outreach programme.DesignThe ERASE-C Campaign is an outreach programme for the screening, diagnosis and group treatment of HCV encompassing 2323 uremic patients and 353 medical staff members from 18 haemodialysis centres. HCV-viremic subjects were linked to care for directly acting antiviral therapy or received on-site sofosbuvir/velpatasvir therapy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 37 publications
0
26
0
1
Order By: Relevance
“…A total of seven studies satisfied our pre-defined selection criteria and were included in the meta-analysis. 4,[17][18][19][20][21][22] The flow diagram for the search strategy is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of seven studies satisfied our pre-defined selection criteria and were included in the meta-analysis. 4,[17][18][19][20][21][22] The flow diagram for the search strategy is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The seven studies that were finally incorporated in the meta-analysis included four single-centre studies (3 from India and 1 from Bangladesh) and three multicentric studies. 4,[17][18][19][20][21][22] One of the multicentric studies was conducted across 22 centres in Europe, North America and Australia, another was conducted in 18 haemodialysis centres of 3 Taiwanese cities, and the third study was conducted in 15 academic centres of Taiwan. 4,21,22 Five of the studies were prospective while the studies by Gaur et al and Liu et al were retrospective.…”
Section: Resultsmentioning
confidence: 99%
“…32 The other studies showed no clinically relevant change in renal function among the majority of CHC patients received both sofosbuvir-based or sofosbuvir-free regimens, even until 24 months of post-treatment 33 or among patients with existing CKD, 34 and is safe and effective for ESRD HCV patients under maintenance hemodialysis. 35 However, long-term effects of direct acting antiviral on renal outcome remains unclear. 36 The limitation of this study is the period of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment rate significantly improved for patients from non-hepatology departments, increasing the in-hospital HCV treatment uptake from 6.4 to 73.9% with the strategy [ 7 ]. We successfully implemented a diagnostic cascade for special patient groups such as those undergoing dialysis and prisoners [ 10 , 23 ]. This study further extended the care cascade to vulnerable cancer patients using an entry-based therapeutic control system before initiating chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Along with many achievements in managing HCV, several measurements have been vigorously implemented over the past decade to achieve the ultimate goal of eliminating HCV. These efforts include amelioration of the epidemic in hyperendemic areas and treatment programs for high-risk groups such as CHC patients undergoing dialysis, people who inject drugs, and prisoners [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%